2022
DOI: 10.1016/j.gim.2021.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation and reporting of large regions of homozygosity and suspected consanguinity/uniparental disomy, 2021 revision: A technical standard of the American College of Medical Genetics and Genomics (ACMG)

Abstract: Disclaimer: This technical standard is designed primarily as an educational resource for clinical laboratory geneticists to help them provide quality clinical laboratory genetic services. Adherence to this technical standard is voluntary and does not necessarily assure a successful medical outcome. This technical standard should not be considered inclusive of all proper procedures and tests or exclusive of other procedures and tests that are reasonably directed to obtaining the same results. In determining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…In particular, many pathogenic CNVs that are highly related to developmental disorders often have incomplete penetrance and variable expressivity, and there are cases in which the phenotype is almost normal with pathogenic CNVs [19][20][21][22]. Additionally, secondary findings include CNVs related to childhood or adult-onset diseases, CNV carriers related to X chromosome recessive diseases, and AOH information that can identify consanguinity between biological parents [23,24]. Therefore, comprehensive genetic counseling that considers these various situations is crucial.…”
Section: Interpretation Of Prenatal Cma Results and Genetic Counselingmentioning
confidence: 99%
“…In particular, many pathogenic CNVs that are highly related to developmental disorders often have incomplete penetrance and variable expressivity, and there are cases in which the phenotype is almost normal with pathogenic CNVs [19][20][21][22]. Additionally, secondary findings include CNVs related to childhood or adult-onset diseases, CNV carriers related to X chromosome recessive diseases, and AOH information that can identify consanguinity between biological parents [23,24]. Therefore, comprehensive genetic counseling that considers these various situations is crucial.…”
Section: Interpretation Of Prenatal Cma Results and Genetic Counselingmentioning
confidence: 99%
“…The offspring of consanguineous relationships were found to have multiple large contiguous homozygous genomic stretches (ROHs) across different chromosomes (Alkuraya, 2010b; Sund et al., 2013), with an increased probability of disease‐causing variants associated with the autosomal recessive disease that were inherited in a common ancestor to be detected in ROHs (Alkuraya, 2010a; Sund et al., 2013). Homozygosity mapping by single‐nucleotide polymorphism microarray can identify these regions where variant analysis could be prioritized especially in genetically heterogeneous conditions, and where disease‐causing variants would simultaneously segregate (Alkuraya, 2010a; Gonzales et al., 2022). In our report, analysis of ROHs suggested that both variants segregated independently rather than simultaneously although both exist in chromosome 3 due to GMPPB not being in the ROH where the SLC25A38 variant was found.…”
Section: Discussionmentioning
confidence: 99%
“…The SNP array can detect isodisomy directly; however, up to one-third of UPD (heterodisomy) cases may be undetectable ( Hoppman et al, 2018 ). Heterodisomy (exactly combined iso- and heterodisomy (mixtures of both subtypes)) may be detected by 1 or more ROHs on a single chromosome that does not include the pericentromeric region ( Gonzales et al, 2022 ). Notably, 12 cases with combined iso- and heterodisomy were detected in our study.…”
Section: Discussionmentioning
confidence: 99%
“…As the results of the prenatal diagnosis were obtained before detailed second-trimester fetal anomaly scans, these families opted for TOP prior to the typical ultrasound presentation of these disorders. When imprinting disorders were excluded, UPD had almost no clinical consequences ( Gonzales et al, 2022 ). However, ROH/UPD fetuses with ultrasound abnormalities showed worse prognoses than those without abnormalities ( Del Gaudio et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%